PENGARUH PRAKTIK MANAJEMEN LABA DAN GOOD CORPORATE GOVERNANCE TERHADAP NILAI PERUSAHAAN PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA - Charlie Charlie (LEMBAGA PENERBIT FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS TRISAKTI, 2017)
The purpose of this study is to examine the effect of corporate governance (GCG) which is proxied through managerial ownership and institutional ownership, as well as earnings management on firm value. The sample used is LQ 45 company with observation period from 2011 to 2015. Data analysis method uses multiple linear regression. The results of this study are that there are positive and significant effects of managerial ownership, institutional ownership and earnings management on firm value.